The Meaning of Da’wah in Rich Short Films Without Wealth: Makna Dakwah Pada Film Pendek Kaya Tanpa Harta - Defa Tri Arnetta (Program Studi Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Mulawarman, 2021)
Da'wah is an activity to spread knowledge of Islam to all corners of the world. With the development of the times, it becomes a challenge for the da'i so that their da'wah can be enjoyed and disseminated more widely. In this digital era, visual media is the most effective tool used to spread da'wah. One of the media that is currently popular is YouTube. The ease of YouTube's popularity needs to be put to good use, such as creating and displaying educational content with Islamic elements, such as films of the religious genre. The researcher analyzed the da'wah contained in rich short films without religious genre treasures on the YouTube channel of Muslim filmmakers to find the meaning of denotation, connotation and myth in the film. The research method used is descriptive qualitative with Roland Barthes' semiotic approach. The type of research used is field research, researchers observe the object directly. The results of this study are that the meaning of denotation in this study is about the description of human life in facing various trials of life in family, neighbors and friends. The meaning of the connotations in the short film Kaya without treasure is that sincerity, gratitude and patience will make us calmer and accept what is. The meaning of the myth in the short film rich without wealth is that alms will make us more grateful for what Allah SWT has given us. The message of moral da'wah is more dominant in this film.